Factors affecting the empathy levels of students of the University of the Philippines College of Pharmacy - Chavez, Joshua Elijah M.
Empathy is known to be an important attribute for health care professional, as this has been shown to be associated with positive outcomes for patients. As such, it is considered as the center of the patient-health care professional relationship. Several studies report that empathy can be developed , even at the level of students. In this study, empathy levels of students of the University of the Philippine college of Pharmacy were measured. Likewise, effects of the different demographic, psychological, and academic factors on empathy were explored. A total of 225 students were randomly selected to participate in this study. The Interpersonal Reactivity Index, which consists of four sub scales, was used to generate scores that correspond to the respondent ' empathy. The results revealed that five factors were significantly associated with any of the sub scales of empathy. Females significantly scored higher than men in the Fantasy and Personal Distress scale. Higher subjective well-being, measured as satisfaction with life, corresponds to an increase in Empathic Concern. Furthermore, extracurricular participation and time spent on organizational work were both shown to be negatively correlated with Personal Distress (p<0.001 and p=0.008 respectively) but positively correlated with Perspective-Taking (p=0.008 and p=0.024 respectively). Significant differences were likewise observed between the Fantasy and empathic Concern scores across the grade weighted average groups. The study demonstrated that empathy possesses a multi-factorial nature, opening the possibility of its deliberate enhancement in the academic setting.